Stavropol Kalmyks in the Swedish Campaign and on Russia’s Western Borders, 1790–1792 - Ramil N. Rakhimov (Oriental Studies)
Introduction. In 1790–1792, Stavropol Kalmyk Host participated in the Russo-Swedish War and patrolled the Belarusian border. The reasons behind the long deployment remain somewhat debatable. Materials and methods. The article focuses on archival documents and published sources. The historical-genetic method proves most instrumental herein, while it is the reconstruction method that yields extended analytical insights into epistolary sources. Results. The Russo-Swedish War of 1788–1790 was attended by three Bashkir regiments, crews of Orenburg Cossacks and Stavropol Kalmyks. The irregular units were to reinforce Russian troops since the army was engaged in the Russo-Turkish War. Furthermore, the former’s involvement was meant to intimidate the enemy. A supporter the Swedish king, Prussia was actively spreading the myth Russia be a country inhabited by ‘barbarians’. The imaginary ‘Kalmyk-Tatar’ threat was declared in Sweden. Since 1789, two Bashkir regiments had been engaged in combat operations. In 1790, Orenburg Cossacks and Stavropol Kalmyks were summoned to reinforce the troops: together they formed a detachment that took part in repelling a Swedish landing operation. The Bashkirs dispatched ‘to horrify’ the enemy units proved brave warriors, and either did reinforcing Stavropol Kalmyks and Orenburg Cossacks which was noted by commanding officers. In 1790, armed hostilities with Prussia and Poland were expected. The newly formed Dvina Army that included two Bashkir and one Mishar regiments, crews of Orenburg Cossacks and Stavropol Kalmyks was to defend the Baltics and Belarus. The sight of ethnic cavalry groups on the border gave rise to rumors about Asian peoples — horse meat eaters and potentially even cannibals. The presence of Bashkirs, Mishars and Kalmyks along the borderline did have certain positive impacts. In July 1792, Russian troops invaded Poland via Volhynia and occupied Warsaw. In September, the Kalmyks, Bashkirs, Mishars and Cossacks were dispatched home. Conclusions. The participation of Stavropol Kalmyks in the Russo-Swedish War and their border service in 1790–1792 was the second successful campaign against European armies. The long expedition of Bashkirs and Mishars, Orenburg Cossacks and Stavropol Kalmyks was the first mass relocation of irregular troops from Orenburg Krai to join Russian field forces. This experience was repeated in the Napoleonic Wars. In 1790–1792, Stavropol Kalmyks — fighting the Swedes and patrolling the border — were simultaneously performing an important task of demonstrating the unity of Imperial Russia’s peoples under Empress Catherine II to Europe.